The influence of partial surface shot peening on fatigue crack growth behaviour of a high-strength ferritic steel - Al-Turaihi, A; Mehmanparast, Ali; Brennan, Feargal (Wiley, 2017)
The effects of partial surface shot peening on the fatigue crack growth behaviour of a ferritic steel have been experimentally investigated in this paper. Dog-bone specimens fabricated from Optim700QL were tested under tension-tension fatigue loads. Three distinct extents of partial shot peening, with respect to the crack tip and specimen symmetry line, were tested. The fatigue crack growth results from these experiments have been compared with those obtained from the same specimen geometry but with no peening. The results show that the residual stress fields formed ahead of the initial notch tip due to the partial peening process play a significant role in the fatigue crack growth behaviour of the material and effectively result in accelerated crack propagation at the midwidth of the specimens. It has been shown in this study that partial peening can lead to a fatigue crack growth rate around twice as fast as that of the unpeened specimen.
Keywords: Fatigue; Fatigue limit; High-strength steel; Residual stress; Shot peening; Surface defect